Control of VOCs from printing press air emissions by anaerobic bioscrubber: Performance and microbial community of an on-site pilot unit. (15th July 2017) - Bravo, D.; Ferrero, P.; Penya-roja, J.M.; Álvarez-Hornos, F.J.; Gabaldón, C.
Abstract: A novel process consisted of an anaerobic bioscrubber was studied at the field scale for the removal of volatile organic compounds (VOCs) emitted from a printing press facility. The pilot unit worked under high fluctuating waste gas emissions containing ethanol, ethyl acetate, and 1-ethoxy-2-propanol as main pollutants, with airflows ranging between 184 and 1253 m 3  h −1 and an average concentration of 1126 ± 470 mg-C Nm −3 . Three scrubber configurations (cross-flow and vertical-flow packings and spray tower) were tested, and cross-flow packing was found to be the best one. For this packing, daily average values of VOC removal efficiency ranged between 83% and 93% for liquid to air volume ratios between 3.5·10 −3 and 9.1·10 −3 . Biomass growth was prevented by periodical chemical cleaning; the average pressure drop was 165 Pa m −1 . Rapid initiation of anaerobic degradation was achieved by using granular sludge from a brewery wastewater treatment plant. Despite the intermittent and fluctuating organic load, the expanded granular sludge bed reactor showed an excellent level of performance, reaching removal efficiencies of 93 ± 5% at 25.1 ± 3.2 °C, with biogas methane content of 94 ± 3% in volume. Volatile fatty acid concentration was as low as 200 mg acetic acid L −1 by treating daily average organic loads up to 3.0 kg COD h −1, equivalent to 24 kg COD m −3 bed d −1 . The denaturing gradient gel electrophoresis (DGGE) results revealed the initial shift of the domains Archaea and Bacteria associated with the limitation of the carbon source to a few organic solvents. The Archaea domain was more sensitive, resulting in a drop of the Shannon index from 1.07 to 0.41 in the first 123 days. Among Archaea, the predominance of Methanosaeta persisted throughout the experimental period. The increase in the proportion of Methanospirillum and Methanobacterium sp. was linked to the spontaneous variations of operating temperature and load, respectively. Among Bacteria, high levels of ethanol degraders ( Geobacter and Pelobacter sp.) were observed during the trial. Graphical abstract: Highlights: A new air biotreatment, namely an anaerobic bioscrubber, was successfully field-scale tested. Cross-flow was the optimal packing for the absorption of printing VOC air emissions. Anaerobic degradation of 1-ethoxy-2-propanol was demonstrated. Volatile fatty acids were not accumulated for an organic loading rate <24 kg COD m −3  bed d −1 . Methanosaeta and Geobacter were distinguished as predominant microorganisms.